Evidence for passive dispersal of ground beetles (Coleoptera: Carabidae) in the Nearctic boreal forest. Issue 1 (2nd January 2021) - Fleming, Kaitlyn J.; Schaefer, James A.; Abraham, Kenneth F.; Smith, M. Alex; Beresford, David V.
ABSTRACT: Passive transport has likely contributed to the post-glacial dispersal of species in temperate regions. However, identifying such processes from patterns can be obscured by confounding environmental conditions. We studied the distribution of ground beetles in Ontario's Far North, a vast (450, 000 km 2 ) and largely intact region, to identify mechanisms that aid in species dispersal when confounding factors, such as temperature, are controlled. We tested a model of passive, riverine dispersal using recent records of flightless and flighted ground beetles from 34 sites across the region. The number of species declined with distance from main watershed rivers, as predicted from our model at the site level. Contrary to expectations, this pattern was evident with flighted species but not flightless species. The opposite pattern, with flightless species displaying a decrease with increasing distance from river, was evident at a regional level. These patterns are consistent with ground beetles carried along rivers since glacial retreat. We surmise that northward dispersal of these invertebrates into the boreal forest has been aided by vegetation and other debris flowing down rivers, including soil from eroded banks in which larvae and pupae reside. Biogeographic inferences, although often subtle, can be supported by broad-scale studies of intact landscapes.